Understanding waste management in the 04 birugo Bukittinggi state elementary school environment - Nigrum, Widian; Yuniarti, Elsa; Razak, Abdul; Handayuni, Linda (Science Midwifery, 2023)
Population growth has an impact on the need for land availability and food production needs. The need for land and food production will increase the amount of waste or leftovers, both from the production and consumption processes, these wastes or leftovers are known as waste. This research was conducted at State Elementary School 04 Birugo Bukittinggi. The method used in this research is direct observation and interviews. The data collected was analyzed descriptively qualitatively and quantitatively by emphasizing the substance of the problem regarding the relationship between variables that influence each other in the social-based waste management process, such as aspects of students and the environment and techniques for using equipment/technology, which influence waste management. The results of this research can be seen from the types of waste found in schools, there are 2 types of waste, namely organic waste with 3 types and inorganic waste with 6 types. Furthermore, the generation of organic waste and inorganic waste obtained a total of 2,978.78 grams of organic waste and 4,214.00 grams of inorganic waste which was calculated for 13 months. As for waste management at the 04 Birugo Bukuttinggi Elementary School, follow up on organic waste by making solid and liquid organic fertilizer.